Imaging Macrophage and Hematopoietic Progenitor Proliferation in Atherosclerosis. Issue 10 (23rd October 2015) - Ye, Yu-Xiang; Calcagno, Claudia; Binderup, Tina; Courties, Gabriel; Keliher, Edmund J.; Wojtkiewicz, Gregory R.; Iwamoto, Yoshiko; Tang, Jun; Pérez-Medina, Carlos; Mani, Venkatesh; Ishino, Seigo; Johnbeck, Camilla Bardram; et al.
Abstract : Rationale: : Local plaque macrophage proliferation and monocyte production in hematopoietic organs promote progression of atherosclerosis. Therefore, noninvasive imaging of proliferation could serve as a biomarker and monitor therapeutic intervention. Objective: : To explore 18 F-FLT positron emission tomography–computed tomography imaging of cell proliferation in atherosclerosis. Methods and Results: : 18 F-FLT positron emission tomography–computed tomography was performed in mice, rabbits, and humans with atherosclerosis. In apolipoprotein E knock out mice, increased 18 F-FLT signal was observed in atherosclerotic lesions, spleen, and bone marrow (standardized uptake values wild-type versus apolipoprotein E knock out mice, 0.05±0.01 versus 0.17±0.01, P <0.05 in aorta; 0.13±0.01 versus 0.28±0.02, P <0.05 in bone marrow; 0.06±0.01 versus 0.22±0.01, P <0.05 in spleen), corroborated by ex vivo scintillation counting and autoradiography. Flow cytometry confirmed significantly higher proliferation of macrophages in aortic lesions and hematopoietic stem and progenitor cells in the spleen and bone marrow in these mice. In addition, 18 F-FLT plaque signal correlated with the duration of high cholesterol diet (r 2 =0.33, P <0.05). Aortic 18 F-FLT uptake was reduced when cell proliferation was suppressed with fluorouracil in apolipoprotein E knock out mice ( P <0.05). In rabbits, inflamed atherosclerotic vasculature with the highest 18 F-fluorodeoxyglucose uptake enriched 18 F-FLT. In patients with atherosclerosis, 18 F-FLT signal significantly increased in the inflamed carotid artery and in the aorta. Conclusions: : 18 F-FLT positron emission tomography imaging may serve as an imaging biomarker for cell proliferation in plaque and hematopoietic activity in individuals with atherosclerosis. Abstract : Supplemental Digital Content is available in the text.